Application of the open corporate system model for the management of administrative accounting of the SACSA Business Group - Inzunza-Mejía, Patricia Carmina (2023)
The objective is to apply an open corporate system model for the control of administrative accounting and the strategic management of income to avoid risks in the network of authorization or financing promoters that it offers SACSA Corporate. With a qualitative methodology, exploratory and descriptive, the case study method was used and the open corporate-operative system model was applied, to identify the driving and constraining forces of the organization's strategic management of sales and profits, which was complemented with the method of systematic analysis of scientific literature in correspondence to the administrative and strategic control of the companies. The findings reveal that the model allows optimizing the management of income and profit control, documenting the process in accounting and financial information reports through the open corporate system with operational and informative characteristics of administrative accounting, which must be closely linked to the technological development systems and human resource training systems. With its implementation, the operationalization of accounting and administrative information is improved, which allows the redefinition of responsibilities and functions of the personnel, in addition to promoting the creation of innovative strategies based on certification, aimed at factors involved in the sales process to obtain greater benefits and to improve the profitability of the company.